Correlation Between the “seeing FWHM” of Satellite Optical Observations and Meteorological Data at the OWL-Net Station, Mongolia - Bae, Young-Ho; Jo, Jung Hyun; Yim, Hong-Suh; Park, Young-Sik; Park, Sun-Youp; Moon, Hong Kyu; Choi, Young-Jun; Jang, Hyun-Jung; Roh, Dong-Goo; Choi, Jin; Park, Maru; Cho, Sungki; et al. (Journal of astronomy and space sciences, 2016)
The correlation between meteorological data collected at the optical wide-field patrol network (OWL-Net) Station No. 1 and the seeing of satellite optical observation data was analyzed. Meteorological data and satellite optical observation data from June 2014 to November 2015 were analyzed. The analyzed meteorological data were the outdoor air temperature, relative humidity, wind speed, and cloud index data, and the analyzed satellite optical observation data were the seeing full-width at half-maximum (FWHM) data. The annual meteorological pattern for Mongolia was analyzed by collecting meteorological data over four seasons, with data collection beginning after the installation and initial set-up of the OWL-Net Station No. 1 in Mongolia. A comparison of the meteorological data and the seeing of the satellite optical observation data showed that the seeing degrades as the wind strength increases and as the cloud cover decreases. This finding is explained by the bias effect, which is caused by the fact that the number of images taken on the less cloudy days was relatively small. The seeing FWHM showed no clear correlation with either temperature or relative humidity.